Turkey and the Possibility of Its Integration into the European Union - Stejskal, Jakub, 1988-; Vysoká škola ekonomická v Praze. Fakulta managementu; Kopřiva, Bohumil; Riley, Steven Del (2011)
The thesis will examine the position of Turkey from the point of view of possible entry into the European Union. The opening part will deal with conditions of its entry, Turkey's relations with other member countries will be outlined as well as the issue of its economic development in the last years. The second part will deal with economic insight, where the country will be examined on the basis of economic data, especially in connection with the new members of the European Union.
Vedoucí práce: Bohumil Kopřiva
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta managementu, 2011
Obsahuje bibliografii
Rok obhajoby 2011
Keywords: hospodářská politika; země Evropské unie; Turecko; management [obor bakal. práce]; bakalářské práce; economic policy; European Union countries; Turkey; bachelor's theses